Stabilization of a General Trophic Model via Nonlinear Feedback Harvesting - Pasand, M. M. Share (Journal of Applied Nonlinear Dynamics, 2026)
Dynamics of population density of species in a trophic food chain with n distinguished members are investigated. A nonlinear feedback harvesting law is proposed to stabilize the coexistence equilibrium point of the system. A method is also proposed to derive the feedback parameters. The proposed dynamical model captures predation, competition, logistic growth and carrying capacity phenomena. An interesting real-world example is included to show the counter-intuitive behavior of the studied system and the effectiveness of the proposed harvesting method.